Escolha de descritores mínimos e estabelecimento de coleções nucleares em Capsicum spp. - SILVA, Waldir Camargos Júnior e (2008)
The plant genetic diversity is a valuable guarantee for possible adversities that can be risking the survival of biological species. Brazil is one of the richest countries in biodiversity of plants, with about 20% of all the existing biodiversity on Earth and around 19% of the agricultural lands in the world. Genetic resources are studied in well-defined stages, such as collecting or introduction, multiplication, preservation/conservation, evaluation/characterization and use. In Brazil, the Empresa Brasileira de Pesquisa Agropecuária manages a national system of curatorship of genetic resources in which more than 250 thousand samples of plants, animals and microorganisms are preserved. The plants of the genus Capsicum (chilli and sweet peppers) are found throughout the national territory, presenting countless kinds, with a great phenotypic and genotypic diversity. Practically all the brazilian states have their own cultivars, but some of them, can be in fact, considered a mere duplicate because, sometimes, the same cultivar is known under different names. Thus, the morphological characterization is a task of great importance to this plant genus so, it is possible to avoid the conservation and maintenance of accessions of similar genomic patterns in germplasm banks. Embrapa Hortaliças has a collection of germplasm of sweet and chilli peppers (Capsicum spp.), which amounts to about 2,500 accessions. These mainly belong to the species C. annuum, C. baccatum, C. chinense and C. frutescens. The morphological characterization of most of these acessions (893) have been carried out in recent years for a series of characters (descriptors) which allow the investigation of the structure of their genetic variability and, from then the proposition of strategies to handle the collection. Considering the need of studies aiming to know, value and use the accessions of the Capsicum spp. Embrapa Hortaliças collection, this research was developed with the objective of describing the accessions and the descriptors available in this collection, in order to search for minimum descriptors and propose core collections for this germplasm bank. The study demonstrated that it is possible to reduce around 50% the number of descriptors currently used in the characterization of the accessions, without significant harm to the representation of the genetic variability of the collection. The factorial correspondence analysis showed to be appropriate for the selection of minimum descriptors, as well as to the proposition of core collections from germplasm banks, characterized, predominantly, by qualitative data. Variables related to the fruit showed great variability in all the germplasm collection, demonstrating that these attributes are important in the genetic discrimination among the accessions. The study also showed that the geographical origin, regardless of the species, is directly associated with the genetic divergence among the accessions in Capsicum spp.